Uma perspectiva analítico-comportamental do desenvolvimento (Brazilian Journal of Behavioral and Cognitive Therapy, 2019)
In this article, I describe how my behavior-analytic perspective on infant and child development evolved andwhat a behavior-analytic theory of development might look like. I begin by describing how my approach toteaching child development courses changed from focusing mostly on behavior analysis to teaching criticalthinking skills that would enable students to evaluate traditional developmental research and theory and thento find a behavior-analytic perspective more appealing. I describe the critical thinking skills I teach students,including nominal fallacy, circular reasoning, reification, and parsimony. Throughout, I contrast a traditionaldevelopmental approach to research and theory with a behavior-analytic approach. In particular, I notedifferences between the between-subjects experimental designs used by developmental researchers and thewithin-subjects experimental designs used by behavior analysts in terms of internal and external validity andtheir implications for theory construction. I argue that, because behavior-analytic theory is inductively derivedfrom decades of experimental analysis, it is in a better position to achieve the goals of prediction, control, andunderstanding and can generate successful technologies of behavior change.
Keywords: behavior analysis; cognitive psychology; developmental psychology; theory; nominal fallacy; parsimony; reification